Panels with nonstationary multifactor error structures - George Kapetanios; Mohammad Hashem Pesaran; Takashi Yamagata (Center for Economic Studies and ifo Institute (CESifo), 2006)
Increasing longevity causes an upward trend in the dependency ratio in many countries. This raises concerns about the financial sustainability of social security schemes, and reform initiatives and proposals abound. It is shown that a fundamental policy choice inevitably arises since a given social security system cannot be maintained by simply indexing retirement ages and benefits to longevity. The political reform process is analysed using the so-called legislative procedure. When longevity increases, the young generation contributes more, and the old generation faces lower benefits and an retirement age that increases more than proportionally to the increase in longevity.
Keywords: D72; H55; J11; J14; J18; 330